Afrotropical weevils of the Cadoderus Marshall generic complex (Coleoptera: Curculionidae: Entiminae: Embrithini). Part 2. Two new species of the genus Sphrigodellus Marshall, 1942 from Udzungwa Mountains, Tanzania - Yunakov, Nikolai (Zootaxa, 2022)
Two new species of the genus Sphrigodellus Marshall, 1942 are described from cloud forests of the Udzungwa Mountains, Tanzania. Sphrigodellus griseus sp. n. from Udzungwa Scarp differs from all known species of the genus by the uniform, grey, marmorate coloration of the body, prementum with four setae, C-shaped lobes of endophallic sclerite, and extremely oblong collum of spermatheca. Sphrigodellus marshalli sp. n. is restricted to the Ukami Forest, differs from other species of the genus by the presence of black glabrous granules on the pronotum and female tergite 8 without setae on posterior margin.